Plastic scintillator-based fibre dosimeters for measurement of X-ray pulses in a clinical setting - Kam, Wern; Ioannou, Andreas; Martyn, Michael; Sullivan, F. J.; Posporis, Andreas; Woulfe, Peter; Kalli, Kyriacos; O’Keeffe, Sinead (My University, 2022)
This work presents the development of plastic scintillator (BCF-10) based optical fibre sensors for medical radiotherapy dosimetry. Two different designs of BCF10 joined to PMMA (Polymethyl methacrylate) fibre were considered, based on simple Plug and Play designs for the rapid and effective assembly of radiation sensors. The first design was a simple butt-coupling arrangement sheathed in tubing, with an outer diameter of <2 mm. The second design explored the coupling joint of a cylindrical protrusion and hollow part of BCF10-PMMA that were achieved using femtosecond laser machining; the purpose of which was to maintain the original 1-mm fibre diameter for the sensor probe. The two fibres were pressed together and sealed with UV curing, hence the reference to a Plug and Play architecture. Both sensors exhibit higher output counts at the higher dose rate (due to the higher number of radiation pulses), although a discernible signal is observed at 50 MU/min for 6 MV, 15 MV energies and both sensors. When comparing both sensors with the different joint coupling designs, the flat surface connection of BCF-10 to PMMA demonstrates slightly higher photon counts compared with the micro-machined sensor (Plug n Play). However, the difference is small and the Plug n Play sensor benefits from the smaller sensor diameter (1 mm diameter), which is suitable for inserting into a small applicator or in-vivo monitoring. In the second section, micro-pulses of X-Ray radiation from Siemens Linear Accelerator (linac) were obtained and compared for two different energies and dose rates. Both of the sensors demonstrate the feasibility to be used for characterisation of X-ray pulses from a clinical linac.
Keywords: Plastic scintillator; fibre dosimeters; X-ray pulses